Luminescent lead coordination polymer and preparation method thereof
By forming coordination compounds with lead ions, the problems of low luminescence efficiency and short life of lead coordination compounds are solved, and high-efficiency and long-life room temperature phosphorescent materials are realized, which has important application value.
Patent Information
- Application Number
- CN202510271353.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-08
- Publication Date
- 2025-05-09
AI Technical Summary
In the prior art, the lead coordination compound has low luminescence efficiency and short life, making it difficult to achieve a high-performance room temperature phosphorescent material.
By using 2-chloronicotinic acid and lead ions to form a coordination compound, the luminescent lead coordination polymer was synthesized by solution stirring, which improved its luminescent efficiency and extended its luminescent life.
It has achieved high luminescence quantum efficiency and long life room temperature phosphorescent materials, with high yield, low cost and wide application prospects.
Smart Images

Figure CN119955119A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of luminescent materials, and in particular relates to a luminescent lead coordination polymer and a preparation method thereof. Background Art
[0002] Depending on the nature of the excited state, photoluminescence is usually divided into two categories: fluorescence and phosphorescence. The lifetime of fluorescence is short, and the lifetime of typical fluorescence is usually in the nanosecond range. The lifetime of phosphorescence is usually longer, generally in the microsecond to millisecond range, or even longer, but it usually needs to be achieved at low temperatures, and room temperature phosphorescence is difficult to achieve. The Stokes shift between the excitation light and the emission light of phosphorescent materials is large, and the emission lifetime is long, which can effectively prevent the interference of short-lived background noise generated by the spontaneous fluorescence of the system and the scattered light of the sample. Therefore, phosphorescent sensors usually have higher selectivity than fluorescent sensors. When fluorescent materials are used as the light-emitting layer in organic light-emitting diodes (OLEDs), there is a technical defect of low internal quantum efficiency (IQE). If phosphorescent materials are used as the light-emitting layer, both triplet excitons and singlet excitons can be fully utilized, thereby achieving an IQE of nearly 100%. Therefore, the design and synthesis of new phosphorescent materials are crucial to the development of high-performance phosphorescent sensors and OLED light-emitting devices.
[0003] At present, the reported phosphorescent coordination compounds are mainly rare earth complexes and precious metal complexes, but the abundance of precious metals and rare earth metals is low and the price is expensive. The main group metal resources are abundant and cheap, and they have extremely high commercial value. The main group metal coordination compounds are good substitutes for precious metal coordination compounds. Lead is an important main group element with low price. 2+ The ion has a large radius and a variable coordination number. When coordinated with an organic ligand having luminescent properties, it can usually produce a lead coordination compound with luminescent properties. However, most of the lead coordination compounds reported so far usually only emit short-lived fluorescence, and long-lived phosphorescent lead coordination compounds are rare. The luminescence efficiency of the few reported phosphorescent lead coordination compounds is generally very low (literature information), which greatly limits their application prospects. Summary of the invention
[0004] In view of the shortcomings of the prior art, the present invention provides a luminescent lead coordination polymer and a preparation method thereof, which utilizes 2-chloronicotinic acid and main group metal ion lead to form a coordination compound to improve the luminescence efficiency and extend the luminescence life, thereby obtaining a new room temperature phosphorescent luminescent material with low cost and high benefit.
[0005] The present invention is achieved by adopting the following technical solutions:
[0006] The preparation method of the luminescent lead coordination polymer of the present invention specifically comprises the following steps:
[0007] Weigh lead acetate trihydrate and 2-chloronicotinic acid;
[0008] Dissolving lead acetate trihydrate in deionized water to obtain a lead acetate solution;
[0009] Add 2-chloronicotinic acid into anhydrous ethanol, stir and dissolve, to obtain a 2-chloronicotinic acid solution;
[0010] Mixing the lead acetate solution and the 2-chloronicotinic acid solution, and stirring to react;
[0011] After the reaction is completed, the luminescent lead coordination polymer is obtained by filtering, washing and drying.
[0012] In some embodiments, the stirring reaction time of the present invention is 1 to 3 hours.
[0013] In some embodiments, the present invention uses deionized water and anhydrous ethanol to wash the filtered solid to obtain a luminescent lead coordination polymer product.
[0014] In some embodiments, the molar ratio of lead acetate trihydrate to 2-chloronicotinic acid of the present invention is 1:2.
[0015] In some embodiments, the present invention filters the material after the stirring reaction to obtain a filter residue and a filtrate; the filter residue is washed with deionized water and anhydrous ethanol, and dried to obtain a white powdery luminescent lead coordination polymer product; the colorless and transparent luminescent lead coordination polymer single crystal obtained after the filtrate is naturally evaporated is used for crystal structure analysis.
[0016] The present invention also provides a luminescent lead coordination polymer prepared by the method, wherein the luminescent lead coordination polymer belongs to an orthorhombic crystal system and a P212121 space group.
[0017] The present invention uses commercially available 2-chloronicotinic acid as a ligand, Pb 2+ The ion is the metal center, and the 2-chloronicotinate lead coordination polymer is synthesized by an easily controlled solution stirring method with a yield of 85%. Its single crystal is obtained by the volatile saturated solution method, and its crystal structure is analyzed by X-ray single crystal diffraction. The product molecular formula is [Pb(2-ClNA)2] n (2-ClNA = 2-chloronicotinic acid). The unit cell parameters of the luminescent lead coordination polymer are α=β=γ=90°. The luminescent lead coordination polymer emits bright cyan light under ultraviolet light. The emitted light is long-life phosphorescence with a luminescence lifetime of 2.76ms and a luminescence quantum efficiency of up to 16.25%.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] The present invention provides a luminescent lead coordination polymer and a preparation method thereof. 2-Chloronicotinic acid is used as an organic small molecule ligand, and the ligand is reacted with metal ions to form a coordination polymer. The luminescent lead coordination polymer prepared by the present invention has a simple synthesis method, high yield, room temperature phosphorescence, a life span of 2.76ms, and a luminescent quantum efficiency of up to 16.25%. It has great application prospects in the fields of chemical sensing and lighting display.
[0020] The preparation method provided by the present invention allows 2-chloronicotinic acid ligand to react with Pb 2+ The ions form a structure with higher rigidity through coordination bonds, and there is no coordination of small molecules such as water molecules in the structure of the luminescent lead coordination polymer of the present invention, so that the vibration non-radiative transition of the system is greatly weakened, so that the product has extremely high luminescence efficiency;
[0021] The lead coordination polymer prepared by the present invention has a Pb 2+ The ions play an important heavy atom effect, promoting the intersystem crossing process between the singlet state and the triplet state of the 2-chloronicotinic acid ligand. The resulting luminescent lead coordination polymer has room temperature phosphorescence properties, which makes the product have important application value in the field of phosphorescent detectors and lighting displays.
[0022] The luminescent lead coordination polymer prepared by the invention has high luminescent efficiency and long luminescent life, and the preparation method is simple and convenient, with high yield, thus reducing the preparation cost of the luminescent material. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The asymmetric unit of the luminescent lead coordination polymer structure of Example 1 of the present invention;
[0024] Figure 2 The Pb in the luminescent lead coordination polymer structure of Example 1 of the present invention 2+ Ionic coordination polyhedron;
[0025] Figure 3 These are two coordination modes of the ligands in the luminescent lead coordination polymer structure of Example 1 of the present invention;
[0026] Figure 4 This is a three-dimensional network structure diagram of the luminescent lead coordination polymer of Example 1 of the present invention;
[0027] Figure 5 This is a thermogravimetric analysis diagram of the luminescent lead coordination polymer of Example 1 of the present invention;
[0028] Figure 6 is the X-ray powder diffraction pattern of the luminescent lead coordination polymer of Example 1 of the present invention;
[0029] Figure 7 This is the infrared spectrum of the luminescent lead coordination polymer of Example 1 of the present invention;
[0030] Figure 8 are the excitation (solid line) and emission (dashed line) spectra of 2-chloronicotinic acid ligand;
[0031] Fig. 9 1 is the excitation (solid line) and emission (dashed line) spectra of the luminescent lead coordination polymer of Example 1 of the present invention;
[0032] Fig.10 This is a luminescence lifetime fitting diagram of the luminescent lead coordination polymer of Example 1 of the present invention;
[0033] Fig.11 is the X-ray powder diffraction pattern of the luminescent lead coordination polymer of Example 2 of the present invention;
[0034] Fig.12 This is the X-ray powder diffraction pattern of the luminescent lead coordination polymer of Example 3 of the present invention. DETAILED DESCRIPTION
[0035] The present invention will be further described below in conjunction with specific embodiments.
[0036] Example 1
[0037] Weigh lead acetate trihydrate and 2-chloronicotinic acid in a molar ratio of 1:2; put the weighed 2-chloronicotinic acid in a beaker, add anhydrous ethanol, stir to dissolve, add lead acetate trihydrate dissolved in a small amount of deionized water, continue stirring for 2 hours at room temperature to obtain a white turbid liquid, filter to obtain a filter residue and a filtrate; wash the filter residue with deionized water and anhydrous ethanol, and dry to obtain a white powdery luminescent lead coordination polymer product with a yield of 85%; the colorless and transparent luminescent lead coordination polymer single crystal obtained after the filtrate is naturally evaporated is used for crystal structure analysis.
[0038] The structure of the prepared luminescent lead coordination polymer was characterized: the single crystal structure of the luminescent lead coordination polymer was determined using a German Bruker APEX IICCD X-ray single crystal diffractometer with Mo Kα rays monochromatized by a graphite monochromator. The sample diffraction points were collected at room temperature using the diffraction light source, and SAINT and SADABS software were used for data restoration and absorption correction respectively. The structure was analyzed using Olex-2 software, and the chemical formula of the luminescent lead coordination polymer was [Pb(2-ClNA)2] n , wherein 2-ClNA=2-chloronicotinic acid. The crystallographic data and structural refinement results of the luminescent lead coordination polymer are listed in Table 1.
[0039] Table 1 Crystallographic data and structure refinement results of the luminescent lead coordination polymer of the present invention
[0040]
[0041] Figure 1 to Figure 4 The asymmetric unit structure diagram of the luminescent lead coordination polymer was drawn by Diamond crystal drawing software based on the single crystal structure analysis results. The asymmetric unit of the luminescent coordination polymer consists of a Pb 2+ ion and two 2-chloronicotinate ligands ( Figure 1 ). Pb 2+ The coordination number of the ion is 7, showing a global coordination mode, and the coordinated atoms are evenly distributed in the Pb 2 + Around ions ( Figure 2 ). The 2-chloronicotinate ligand binds to Pb in two ways. 2+ Ionic coordination, one is a carboxyl group connecting two Pb with a bidentate bridge 2+ ion, N atom and another Pb 2+ Ion coordination; the other is that the carboxyl group is connected to three Pb 2+ Ion coordination, such as Figure 3 All Pb 2+ The ions are connected by 2-chloronicotinate ligands containing N1 to form a one-dimensional chain structure along the a axis, and the one-dimensional chain is further connected by 2-chloronicotinate ligands containing N2 to form a three-dimensional network structure ( Figure 4 ). The three-dimensional network structure is formed by Pb-O and Pb-N bonds and has extremely high stability, which is also proved by the thermogravimetric analysis results. Figure 5 As shown, the lead coordination polymer begins to decompose when heated to 270°C in an air atmosphere.
[0042] In order to characterize the phase purity of the luminescent lead coordination polymer, the standard X-ray powder diffraction pattern of the luminescent lead coordination polymer was fitted using Mercury software based on the single crystal structure data. Figure 6 As shown, the diffraction peak position of the experimentally synthesized luminescent lead coordination polymer powder is consistent with the diffraction peak position of the single crystal simulation, indicating that the synthesized product has high phase purity.
[0043] In order to further verify the results of structural analysis, the infrared spectrum of the luminescent lead coordination polymer product was measured using the solid potassium bromide tablet method, such as Figure 7 As shown in the infrared spectrum of the product, there is no strong absorption peak of carbonyl (C═O) stretching vibration in 2-chloronicotinate ligand, indicating that the carboxyl group in the ligand is closely related to Pb 2+ The ions are coordinated; at 1586 and 1382 cm -1 The strong absorption at 3073cm is the asymmetric and symmetric stretching vibration of the carboxyl group of the coordinated ligand. The pyridine ring skeleton vibration of the ligand is also located at this position. -1 The weak absorption at 3425 cm is the CH stretching vibration on the pyridine ring. -1The strong absorption at is the stretching vibration of hydroxyl (-OH), which is caused by trace water in potassium bromide.
[0044] Under ultraviolet light, the 2-chloronicotinic acid ligand and the luminescent lead coordination polymer emit blue-violet light and cyan light, respectively. Figure 8 The excitation and emission spectra of 2-chloronicotinic acid ligand are shown. The optimal excitation wavelength is 340 nm, and the emission peak is located at 385 nm. The luminescence lifetime at this wavelength is measured to be 2.85 ns, which is a typical fluorescence. The luminescence quantum efficiency of 2-chloronicotinic acid ligand is 10.92%. Fig. 9 The excitation and emission spectra of the luminescent lead coordination polymer product are shown in Figure 2. The optimal excitation wavelength is 340nm. With 340nm as the excitation light, the emission spectrum of the product is broadband emission, covering the entire visible light region. The luminescence peak is located at 510nm, which is significantly shifted compared to the ligand. The lifetime of the luminescence at 510nm is measured to be 2.76ms ( Fig.10 ), which is a typical phosphorescence. The quantum efficiency of the luminescent lead coordination polymer product is measured to be about 16.25%, which is much higher than the reported lead coordination polymers. Most of the similar lead complexes reported so far can only emit fluorescence, and only a few can emit phosphorescence, and the luminescence quantum efficiency is often less than 5%, and very few are close to 10%. The luminescent lead coordination polymer disclosed in the present invention can not only emit room temperature phosphorescence, but also has a greatly improved quantum yield, which is significantly advanced.
[0045] Example 2
[0046] Weigh lead acetate trihydrate, 2-chloronicotinic acid, and sodium hydroxide in a molar ratio of 1:2:2, place 2-chloronicotinic acid in a beaker, add anhydrous ethanol, stir to dissolve, then add sodium hydroxide, stir at room temperature for half an hour, then add lead acetate trihydrate dissolved in a small amount of deionized water, continue stirring for 2 hours, and obtain a white turbid liquid, filter to obtain a filter residue, wash the filter residue with deionized water and anhydrous ethanol, and dry to obtain a white powdery luminescent lead coordination polymer [Pb(2-ClNA)2] n The yield is about 46%. The phase purity of the product was characterized by X-ray powder diffraction. Fig.11 As shown in the figure, the diffraction peak position of the experimentally synthesized luminescent lead coordination polymer powder is consistent with the diffraction peak position of the single crystal simulation, and no impurity peak appears, indicating that the synthesized product is a luminescent lead coordination polymer [Pb(2-ClNA)2] n .
[0047] Example 3
[0048] Lead acetate trihydrate and 2-chloronicotinic acid were weighed in a molar ratio of 1:2, anhydrous ethanol was added, and the mixture was evenly stirred. The mixed system was transferred to a stainless steel reactor with a polytetrafluoroethylene liner, and the reactor was placed in a blast drying oven and heated to 150°C. After reacting for 1 day, the oven was closed and naturally cooled to room temperature. After filtering, the residue was washed with deionized water and anhydrous ethanol, and dried to obtain a white powder product, which was the luminescent lead coordination polymer [Pb(2-ClNA)2] n The yield is about 35%. The phase purity of the product was characterized by X-ray powder diffraction. Fig.12 As shown in the figure, the diffraction peak position of the experimentally synthesized luminescent lead coordination polymer powder is consistent with the diffraction peak position of the single crystal simulation, and no impurity peak appears, indicating that the synthesized product is a luminescent lead coordination polymer [Pb(2-ClNA)2] n .
[0049] It should be noted that the above are only some specific embodiments of the present invention. Obviously, the present invention is not limited to the above embodiments, and other variations are possible. All variations directly or indirectly derived from the disclosure of the present invention by those skilled in the art should be considered as the protection scope of the present invention.
Claims
1. A luminescent lead coordination polymer, characterized in that The chemical formula of the luminescent lead coordination polymer is [Pb(2-ClNA)2] n , wherein 2-ClNA=2-chloronicotinate; the crystal of the luminescent lead coordination polymer belongs to the orthorhombic system P212121 space group.
2. The luminescent lead coordination polymer according to claim 1, characterized in that: The unit cell parameters of the luminescent lead coordination polymer are α=β=γ=90°.
3. The method for preparing the luminescent lead coordination polymer according to claim 1 or 2, characterized in that: The following steps are involved: Weigh lead acetate trihydrate and 2-chloronicotinic acid; Dissolving lead acetate trihydrate in deionized water to obtain a lead acetate solution; Add 2-chloronicotinic acid into anhydrous ethanol, stir and dissolve, to obtain a 2-chloronicotinic acid solution; The lead acetate solution and the 2-chloronicotinic acid solution are mixed and stirred for reaction. When the reaction is completed, a luminescent lead coordination polymer is obtained.
4. The preparation method according to claim 3, characterized in that: The reaction was stirred at 20-30°C for 1-3 hours.
5. The preparation method according to claim 3, characterized in that: The method also includes filtering after the reaction is completed, and washing the filter residue with deionized water and anhydrous ethanol to obtain the luminescent lead coordination polymer.